Comparing serum ferritin levels during COVID-19 infection and recovery period in pediatric patients with transfusion-dependent thalassemia, a single-center study - Marhaeni, Wulandewi; Felicia, Fabiola Vania; Sumadi Jap, Arvin Leonard; Hartoyo, Edi; Andayani, Pudji (Frontiers in Medicine, 2023)
Background Ferritin has been recognized as a predictor of severity among Coronavirus-19 disease (COVID-19) patients. Studies have shown higher levels of ferritin in patients with COVID-19 than in healthy children. Patients with transfusion-dependent thalassemia (TDT) basically have high ferritin level due to iron overload. It is uncertain whether serum ferritin level in these patients is associated with COVID-19 infection. Objective To evaluate ferritin levels in TDT with COVID-19 before, during, and after the course of infection. Methods This retrospective study enrolled all TDT children with COVID-19 infection that were hospitalized in Ulin General Hospital Banjarmasin during the COVID-19 pandemic (March 2020 to June 2022). Data were collected from medical records. Results There were 14 patients included in this study, 5 patients had mild symptoms and 9 patients were asymptomatic. The mean of hemoglobin level upon admission was 8.1 ± 3 g/dL and serum ferritin level were 5148.5 ± 2651.8 ng/mL. The average serum ferritin level during COVID-19 infection was 2373.2 ng/mL higher than before infection and then decreased by 952.4 ng/mL after infection. We found no association of increasing serum ferritin with patients’ symptoms (p = 0.27). The severity of anemia also was not correlated with the presentation of COVID-19 infection (p = 0.902). Conclusion Serum ferritin levels in TDT children may not reflect disease severity or predict poor outcomes during COVID-19 infection. However, the presence of other co-morbid conditions/confounders warrants cautious interpretation.